1993
DOI: 10.1161/01.str.24.7.1029
|View full text |Cite
|
Sign up to set email alerts
|

Optimality principles and flow orderliness at the branching points of cerebral arteries.

Abstract: Background and Purpose: The cerebral arteries present an optimum blood flow/vessel radius relation. However, branch angles may vary widely in the cerebral arteries because the parametric optimization of branch angles is irrelevant in terms of energy cost. The position of the flow divider in extracranial arteries has been suggested to be optimum in flow orderliness. No data exist on the flow divider of cerebral arteries. Thus, we hypothesized that in the cerebral arteries the apex of the bifurcations, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…The studies by Rossitti and Lofgren 28,35 demonstrated that the branching angles of cerebral arteries may vary widely and that the apex of the bifurcation may lie in a nonoptimal position relative to the dividing streamline of the flow in the parent vessel, resulting in turbulence, vibrations, and increased shear stress on the vessel wall at the apical region, despite the fact that the blood flow/vessel radius relation is optimal. If aneurysm initiation or progression is related to the bifurcation angle at the vascular divider, then the balance of hemodynamic forces responsible likely will be altered by the stent-induced remodeling described in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Rossitti and Lofgren 28,35 demonstrated that the branching angles of cerebral arteries may vary widely and that the apex of the bifurcation may lie in a nonoptimal position relative to the dividing streamline of the flow in the parent vessel, resulting in turbulence, vibrations, and increased shear stress on the vessel wall at the apical region, despite the fact that the blood flow/vessel radius relation is optimal. If aneurysm initiation or progression is related to the bifurcation angle at the vascular divider, then the balance of hemodynamic forces responsible likely will be altered by the stent-induced remodeling described in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…76 Deviations or alterations from optimal architecture are speculated to result in impaired microcirculatory transport, reduced efficiency, and, thereby, a greater risk of vascular damage. [76][77][78] With innovative technology in retinal photography and computing image processing techniques, new computer-based programs were developed ( Figure S3B) to perform objective and quantitative assessment of novel classes of retinal geometrical and branching parameters, such as tortuosity, fractal dimension, branching angles, and vascular length:diameter ratio reliably and rapidly ( Figure S3C through S3E in the online-only Data Supplement). Examining the branching pattern of the retinal vasculature may indicate the optimal state of the retinal microcirculation and provide additional cardiovascular risk information to enable better predictive ability of cardiovascular outcomes.…”
Section: Advances In the Retinal Vascular Imaging Technologies Assessmentioning
confidence: 99%
“…11 An optimal arrangement of branching and bifurcation sites in the cerebral vasculature is essential to preserve minimum energy expenditure along the network by maintaining constant wall shear stress (WSS) across daughter and parent vessels. 11,25 This vascular optimality principle has been shown to generally apply to the cerebral circulation 11,19,20 and implies a relative optimal bifurcation angle depending on the relative sizes of the daughter branches. Consequently, changes in vessel design at bifurcations are intrinsically linked to altered hemodynamic forces at the apex and, as such, to a possible increased risk of IA formation.…”
Section: ©Aans 2014mentioning
confidence: 99%